A REVIEW ON GLIMEPIRIDE VS TENELIGLIPTIN AS A SECOND-LINE DRUG FOR THE TREATMENT OF TYPE 2 DIABETES MELLITUS - Karthickeyan, K.; Saara, A.F.; Gopal, K.; Karthick, S.; Ashi, A.N. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2023)
Type 2 diabetes mellitus (T2DM) is a condition caused by reduced insulin sensitivity. Those above the age of 45 have an increased risk of developing type 2 diabetes. Oral hypo- glycaemic agents are used to treat type 2 diabetes. Metformin is usually the initial therapy and if it is still insufficient, a second oral medication of a different class will be added. Whereas sulfonylureas and dipeptidyl peptidase-4 inhibitors are the most used second-line drug categories for type 2 diabetes mellitus. Sulfonylureas are used to control hyperglycemia and the glycated haemoglobin A1C (HbA1c) levels can be lowered by 1% to 1.25% when using sulfonylurea, making them just as effective as other options. Mainly glimepiride remains the most widely used sulfonylurea in type 2 diabetes mellitus. Glimepiride enhances glycemic control although glimepiride stimulates endogenous insulin secretion, causing hypoglycemia also causes weight gain, which might complicate diabetes therapy. DPP-4 is a widely distributed enzyme that regulates incretin hormones, which regulate glucose homeostasis by boosting insulin production and lowering glucagon secretion. When compared to other DPP-4 inhibitors, teneligliptin has a unique J-shaped or anchor-locked domain structure because of which it has a potent inhibitory effect on the DPP-4 enzyme and has a low IC50, high potency, and fewer side effects. It is the only DPP-4 inhibitor with a prolonged half-life. Teneligliptin was found to improve blood glucose levels over 24 hours such as reducing the postprandial insulin requirement and reducing glucagon secretion. Thus, compared to glimepiride, teneligliptin is a better choice as a second-line drug for type 2 diabetes mellitus after metformin usage, irrespective of the patient's age and gender.